Analysis of the impacts on unemployment rates from the application of policies to facilitate access to the first job in the 2016-2018 period in Colombia (2021)
Colombia is a developing country and has many challenges to face to continue growing, developing and ensuring the well-being of its population is fundamental, one of the main challenges for social development is to attack unemployment in the Colombian population, to This, the Colombian state has been working by implementing a series of public policies and within these same the creation of programs that are focused on promoting access to the first and youth entrepreneurship, eliminating barriers in the public sector so that professionals without experience have a chance to enter the job market.